FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN GEJALA DERMATITIS KONTAK PADA PEKERJA BENGKEL DI KELURAHAN MERDEKA KOTA MEDAN TAHUN 2015 - Sabrina Hardianty; Lina Tarigan; umi salmah (Lingkungan dan Kesehatan Kerja, 2015)
ABSTRACT The objective of the research was to find out the correlation of ages, working hours, personal hygiene, the use of Personal Protective Device (APD), and the length of service with the contact dermatitis symptoms in workshop workers at Merdeka village, Medan, in 2012. The research was analytical with cohort design. There are 7 workshop with 34 workers as the population and 17 workers as the sample taken by inclusion criteria. The data were gathered by conducting interviews, questionnaires and observation by using observation sheets to find out how many workers that suffered from the symptoms of contact dermatitis.  A statistic test was used to analyse the Exact Fisher test correlation between independent variables and dependent variable. The distribution frequency showed that there were 14 (82.4%) workshop workers who suffered  from the symptoms of contact dermatitis caused by  battery acid contact and 5 of them suffered from gasoline and lubricating oil. The result of statistic test showed that there was  significant correlation between the length of service and the symptoms of dermatitis at P-value = 0.029, while the factors of working hours, personal hygiene, and the use of APD did not have any significant correlations. It is recommended that the workshop workers keep themselves clean during working hours, apply good personal hygiene, and try to avoid direct contact with chemical substances in workshop by using complete APD such as gloves.